Investigating the meteorological factors influencing upper respiratory tract infections: An observational study - Yeşim Yüksel; Cihan Bedel; Fatih Selvi; Okkes Zortuk; Yusuf Karanci (Journal of Preventive and Complementary Medicine)
Background: Upper Respiratory Infections (URIs) rank among the most prevalent illnesses affecting people globally. Understanding the environmental factors that contribute to the transmission of these infections is essential for effective public health planning and intervention strategies.Objective: This study aims to explore how various meteorological conditions impact the incidence of URIs across different seasons.Methods: We conducted a retrospective observational study involving patients who visited a tertiary education and research hospital in 2023. Meteorological data for the region served by Antalya Training and Research Hospital was collected from January 1 to December 31, 2023. We gathered information on air temperature, dew point, weather conditions, wind speed, and atmospheric pressure, correlating these variables with the number of URI cases. Statistical analyses were performed using IBM SPSS version 27, employing chi-square tests, t-tests, ANOVA, and linear regression.Results: Our findings revealed significant seasonal variations in cases of URIs, with the highest average number occurring in spring and the lowest in autumn. January recorded the peak number of cases, while July experienced the fewest. Significant differences were observed among the seasons (F: 75.397, p < 0.001; Post Hoc Tukey: Spring > all, Summer > Autumn, Winter > Autumn). Correlation analysis demonstrated a negative relationship between URI cases and air temperature, dew point, and wind speed, while changes in atmospheric pressure showed a positive correlation (r values: -0.542, -0.384, -0.038, and 0.440, respectively).Conclusions: The incidence of URIs varies throughout the year, demonstrating a negative correlation with air temperature, dew point, humidity, and wind speed, while showing a positive correlation with changes in atmospheric pressure. These findings highlight the significant impact of meteorological factors on the prevalence of URIs, indicating that seasonal and climatic conditions play a crucial role in the spread of these infections. Further prospective multicenter studies are required to validate these results.